(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Modern education recognizes the importance of hands-on learning for engaging students effectively. Robotics through the use of Arduino provides an avenue for hands-on learning that cultivates interdisciplinary skills and problem-solving abilities relevant to all students, irrespective of their academic field, encouraging creativity, collaboration, and adaptability in a technology-driven world. This study investigates the perceived acceptability of the Arduino platform in facilitating the learning of robotics among senior high school students. This study utilized quantitative approach through the descriptive-survey research, gathering data from 143 respondents using an adapted questionnaire. Weighted mean and standard deviation was used to describe their level of acceptability to the Arduino platform, while t-test and analysis of variance (ANOVA) were used to test significant differences in their acceptance when grouped according to their grade level and strand respectively. The findings indicate that Arduino is highly accepted by students in terms of educational efficiency, engagement and motivation, learning outcomes, inclusivity, long-term relation, and research requirement. This indicates that they perceive the platform can effectively help in enhancing their learning experience in robotics. Moreover, Grade 11 and Grade 12 students’ do not have significant differences in their acceptability. Meanwhile, there is a significant difference in terms of inclusivity between STEM and GAS-Engineering, GAS-Health, and ABM strands, highlighting that the latter perceive the platform as more inclusive than the former. Overall, the study highlights the potential of Arduino as a valuable tool for enhancing robotics education in senior high school. It offers benefits in terms of educational effectiveness, engagement, and long-term learning opportunities. The researchers recommend the need to address challenges related to inclusive use of Arduino, ensuring that it is accessible and engaging for students from all academic backgrounds.